(untitled) (Journal of the College of Languages (JCL), 2020)
Shmuel Yosef Agnon, a well-known Jewish writer, wrote many literary works, including poetry, story, etc. In the field of story, this writer used two areas: the first: a simple exterior, and the second: an inner full of secrets and mysteries. This area is common when Agnon is affected by his symbolic method of purpose. In his productions, we find the political and historical significance embodied in his characters, where there is almost no story without it. Agnon and all his productions gave the character a large area, Agnon’s characters often play the center and cornerstone in those productions, where the author dealt deeply and stated the fines details of the external and internal of that character. This has greatly affected the form and type of production according to the roles of those characters. In this research, we focused on his use of the personality of women in his stories. The woman has occupied a large space in these stories, and as is known about Agnon, he dealt with the character of women in his symbolic style, which covers most of his work, has transferred the figure of women mentioned in the Torah and met with Jewish women characters somewhat similar in his stories, and the purpose of this is to add religious dimension to those characters and then to the events of the story. At other times, we see those Western women depicted as symbols of the enemies of Jews whether they were people or countries. In other stories, Agnon depicts modern Jewish women who contribute to the building of a new home land. In his stories, Agnon gave women different roles in historical, political, religious aspects, and so on. The purpose of all this is to draw the attention and to have influence the Jewish reader through this important angle. It is not surprising that using the female character gives the literary output a kind of suspense, especially when the writer sheds light on the effectiveness of women in society and be a cornerstone in building a family. Or that women have negative functions in their society, which is reflected on the course of events. When we follow these stories we see that most of them are stories with real events give the reader an impression of an interesting objectivity, The matter which Agnon wanted to influence the reader of those works. שמואל יוסף עגנון, הסופר היהודי המפורסם כתב יצירות רבות, וביחוד הסיפורים. בעבודת המחקר הזה התמקדתי בנושא כך כך חשוב שהוא השתמשותו במוטיב דמות האשה בסיפוריו, והשפעתה באופי דמויותיו. ידוע שעגנון הוא סימבוליקן גדול. סיפוריו מתפשרים בשני מישורים- האחד החיצוני, פשוט, והשני פנימי מלא רזים ורמזים. ביצירותיו של עגנון אנו רואים משמעות לאומית-היסטורית טמונה בדמות האשה. גם כן אנו רואים את הסמל הפוליטי של האשה בסיפוריו. גם כן הפשר של רוב סיפורי עגנון, במישור סימבולי, בוודאי הוא לאומי-דתי. הסיפורים האלה ניתנו להתפרש כביטוי לשלילת הגלות מצד עגנון. בעבודת המחקר הזה השתמשתי בסיפורים רבים למשל: האדונית והרוכל, ספור פשוט, עגונות, תמול שלשום..ועוד.